Physical and social availability of alcohol for young enlisted naval personnel in and around home port - Ames Genevieve M; Moore Roland S; Cunradi Carol B (BMC, 2007)
Abstract Background Heavy alcohol consumption rates are higher in the young adult military enlisted population than among civilians of the same age. The literature on alcohol availability, both generally and specifically with respect to work-related drinking, establishes clear links between ease of access, alcohol consumption rates and alcohol-related problems. Methods In this paper, a qualitative analysis of 50 semi-structured interviews with U.S. Navy personnel was combined with quantitative findings from a mail survey of 713 young enlisted men and women in order to shed light on alcohol availability and its correlates in the home port environments of young adult enlisted personnel. The interviews were analyzed by two anthropologists seeking recurring themes or topics related to alcohol availability. These qualitative data were contextualized by descriptive statistics of the survey responses regarding ease of obtaining alcohol on and around naval bases, and from friends in and out of the Navy. Results Findings associated with social and physical availability of alcohol include low prices in Navy Exchange base stores, frequent barracks parties, drink promotions in bars surrounding bases, and multiple opportunities for underage drinking despite age limits on alcohol purchases and official efforts to deglamorize alcohol use in the Navy. Both qualitative and qualitative findings suggest that respondents found alcohol and opportunities to drink overwhelmingly available in both on-base and off-base settings, and from friends both in and out of the Navy. Conclusion There is qualitative and quantitative evidence for extensive physical and social availability of alcohol in and around bases for young adults in the military. Policy implications include raising the presently tax-free alcohol prices in base stores and enforcing existing policies regarding underage drinking, particularly the provision of alcohol by people of legal drinking age, and by bars in and around bases. Cooperative preventive efforts with surrounding communities also offer promising ways for bases to reduce alcohol availability for young adult servicemembers.